High break hit a print public service announcement campaigning against drug addiction - Kuan, Kate Danielle D.
High break hit: a print public service announcement campaigning against drug addiction is a print production thesis that created public service announcement using print media, posters in particular, to promote the advocacy against the use of addictive drugs without the use of scare tactics like how addiction is depicted in common anti-drug addiction campaign posters, and to provoke action from the general public. Effective poster making was applied in designing the posters, including effective taking photographs, choosing the right font, matching the colors with the themes, making strong tagline, and creating catchy slogans, to avoid using scare tactics, teens were asked where they focus their attention on instead of trying out drugs. Their answers were summarized into three categories: (1) Academics, (2) Talents, and (3) Athletics. These were used as the main themes for the posters as these embody the areas in which every person can excel at if they continue living healthily. The models in the photographs are high school and college student themselves; hence they represent my target audience. The aim was to make simple posters that could give practical suggestions on how to fight or avoid the problems that might possibly lead to dependency on illegal drugs. The photos gave answers to some problems related to drug addiction. The slogans came from common dialogues from movies or TV series that are related to drug addiction. The tagline was direct invitation to join the advocacy. The colors chosen for every poster complement the entire theme and feel of the poster. Every element of the poster was considered, and everything was weaved together in order to create effective campaign materials. This print public service announcement is against the use of illegal drugs. This will extend help to the people affected by drug addiction, and will discourage non-addicts to never try taking addictive drugs. This work will help the local office of PDEA in their campaign to have a drug-free community. New and more effective posters are helpful when they handle lectures and seminars in schools, workplaces, and other communities